Pattern of morbidity and mortality among neonates admitted to neonatal intensive care unit in tertiary care centre, western Nepal - K.C., Namrata; Shrestha, Bandana; Bhattarai, Arjun; Paudel, Shankar; Subedi, Nabraj (Journal of Gandaki Medical College-Nepal, 2021)
Background: The objective of this study was to determine the disease pattern and outcome of diseases in neonatal intensive care unit (NICU) as the common causes of mortality and morbidity in our region are preventable.Methods: The retrospective study was carried out in 1041 newborns admitted from 1st August 2019 to 30th July 2020 in Gandaki Medical College Teaching Hospital in Western Nepal. Age, sex, gestational age, diagnosis at admission, outcome of admitted newborns were the main variables under study. Data was entered and analyzed using SPSS 20 version.Result: Among 1041 newborns, 599 (57.54%) were male and 442(42.46%) were female. 1028(98.75%) were born in hospital while 8(0.77%) were born at home and 5(0.48%) in ambulance. The majority 610 newborns were admitted during the first 24 hours of life. Infection and hyperbilirubinemia were the main reasons for admission (44.96% and 23.15 % respectively), followed by prematurity (9.51%) and Birth Asphyxia (9.13%). A total of 831patients (79.83%) were improved and discharged, 79(7.59%) were discharged on request, 61(7.59%) left against medical advice, 34 (3.26) were referred and 36 (3.46%) expired. The major causes for neonatal mortality were prematurity (44.45%), Sepsis (27.78%), and Birth Asphyxia (13.89%) respectively. Among the expired neonates, 24(66.67%) were outborns and 12(33.33%) were inborns and majority 27(75%) expired at the age between 24-48 hours of life.Conclusions: Infection was the leading cause of morbidity and prematurity the leading cause of mortality in the neonatal care unit. This is preventable with antenatal care, training of manpower and procurement of necessary equipments.